MEASURING THE URGENCY OF A DIGITAL RUPIAH: A SOCIO-LEGAL REVIEW - Firdaus, Sendy Pratama (Journal of Central Banking Law and Institutions, 2025)
This study evaluates the necessity of a Digital Rupiah, Indonesia’s central bank digital currency (CBDC), by addressing issues in the cryptocurrency system, including tracking, third-party involvement, and instability. The socio-legal methodology employed in this study examines the impact of CBDC policies on the social spheres associated with the widespread implementation of a Digital Rupiah through its approaches, including normative, contextualised, independent critical analysis, and comparative analysis. By examining the potential legal and social implications of a Digital Rupiah in Indonesia, this study assesses the potential legal shifts in normative habits that may result from its implementation. It investigates the social needs that could be met through the widespread adoption of a Digital Rupiah. The findings were evaluated using bounded rationality to determine whether there is an urgent need for a Digital Rupiah in Indonesia. The author argues that studies on CBDCs in Indonesia have mainly focused on systems and policy development. In contrast, this study extends this discussion by examining the pressing need for CBDCs, as outlined in the Digital Rupiah White Paper. This study argues that the socio-legal perspective adopted is distinct from prior studies, which have primarily focused on the design of systems and policies. It emphasises the importance of the legal aspects of CBDCs in general.